A New Synthesized Microalloys Steel ODS of High Amplitude Ultrasonically Irradiation - Silalahi, Marzuki; Wicaksana, Hanif Abdurrahman; Aziz, Ferhat; Ahda, Syahfandi; Iskandar, Mohamad Riza (Makara Journal of Technology, 2019)
Micropowders of oxide-dispersion-strengthened (ODS) steel have been synthesized using the ultrasonic irradiation method with variations in amplitude. The ultrasonic irradiation process is performed for 50 h at a frequency of 20 kHz with 40%, 50%, and 60% amplitudes in toluene solution. The formation of Fe-Cr microalloys in the preparation of Fe- 15Cr-0.5Y2O3 powder was analyzed using SEM-EDS, X-ray diffraction (XRD), and TEM-EDS. The percentage of Fe- Cr phase mass fraction of ODS steel micropowder formed during ultrasonic irradiation with 40%:50%:60% amplitude was 12.2%:34.1%:22.1%, with 25.67:77.02:38.51 nm crystallite size. The crystallite size at 50% amplitude was the largest, and the diffusion process of Fe-Cr-Y2O3 microparticles was most dominant at 50% amplitude. The Fe and Cr phases are still present when the ODS particles successfully dispersed in the main particle.